Brainstem Organoids From Human Pluripotent Stem Cells - Eura, Nobuyuki; Matsui, Takeshi K.; Luginbühl, Joachim; Matsubayashi, Masaya; Nanaura, Hitoki; Shiota, Tomo; Kinugawa, Kaoru; Iguchi, Naohiko; Kiriyama, Takao; Zheng, Canbin; Kouno, Tsukasa; Lan, Yan Jun; et al. (Frontiers in Neuroscience, 2020)
The brainstem is a posterior region of the brain, composed of three parts, midbrain, pons and medulla oblongata. It is critical in controlling heartbeat, blood pressure and respiration, all of which are life-sustaining functions, and, therefore, damages to or disorders of the brainstem can be lethal. Brain organoids derived from human pluripotent stem cells (hPSCs) recapitulate the course of human brain development and are expected to be useful for medical research on central nervous system disorders. However, existing organoid models are limited in the extent hPSCs recapitulate human brain development and hence, are not able to fully elucidate the diseases affecting various components of the brain such as brainstem. Here, we developed a method to generate human brainstem organoids (hBSOs), containing midbrain/hindbrain progenitors, noradrenergic and cholinergic neurons, dopaminergic neurons, and neural crest lineage cells. Single-cell RNA sequence analysis, together with evidence from proteomics and electrophysiology, revealed that the cellular population in these organoids were similar to that of the human brainstem, which raises the possibility of making use of hBSOs in investigating central nervous system disorders affecting brainstem and in efficient drug screenings.